English English - Afwan Faizin; Khamami Zada (Institut Agama Islam Negeri Curup, 2026)
This article examines the radical transformation of the Saudi Arabian legal system under Vision 2030, marking a fundamental shift from the supremacy of traditional judicial interpretation to the codification of state positive law. The analysis focuses on Crown Prince Mohammed bin Salman’s (MBS) epistemological maneuver to limit the authority of